Attitudes of people with multiple sclerosis toward brain donation - Marrie, Ruth Ann; Kosowan, Leanne; Cutter, Gary R.; Fox, Robert J.; Salter, Amber (Frontiers in Neurology, 2023)
Objective: Research directly examining brain tissue has played an important role in understanding the pathology and pathogenesis of multiple sclerosis (MS) and other diseases of the central nervous system. Such research relies heavily on donations of post-mortem brain tissue yet little is known about the attitudes of people with multiple sclerosis (MS) about brain donation. We aimed to assess the attitudes of people with MS toward brain donation, their preferences related to discussions of brain donation, and factors associated with attitudes toward brain donation including sociodemographic and clinical characteristics, health literacy and religiosity. Methods: In a cross-sectional study, we surveyed participants in the North American Research Committee on Multiple Sclerosis (NARCOMS) Registry regarding their attitudes toward brain donation, reasons for participating or not participating in brain donation, and related communication preferences. We used multivariable logistic regression analyses to test factors associated with attitudes regarding brain donation. Results: Most of the 4,520 participants were women (80.8%), self-identified as white (88.1%), with a post-secondary education, functional health literacy and moderate-severe disability. Sixty-two percent of participants would consider brain donation. Factors associated with considering brain donation included female gender, having a post-secondary education, being physically active, having moderate-severe disability and more comorbidities, and alcohol intake. Seventy-five percent of participants indicated that they preferred to receive information regarding brain donations from physicians. Conclusion: Two-thirds of people with MS would consider brain donation. People with MS desire to hear about brain donation from their health care providers rather than other sources.